Forensic importance of intraoral photographs for human identification in dental autopsies - a case report - Rhonan Ferreira Silva; Matheus Felter; Pedro Henrique Moreira Paulo Tolentino; Michelle Gouveia Benício de Araújo Andrade; Livia Graziele Rodrigues; Ademir Franco (Bioscience Journal, 2017)
Human identification may be achieved through fingerprint, teeth and DNA analyses. In these approaches, identification is given comparatively - between antemortem (AM) and postmortem (PM) data. Intraoral photographs, commonly used in Orthodontics, represent a source of dental identifiers in Forensic Dentistry. The present study aims to report a case of human identification founded on the analysis of intraoral photographs. An unknown human body was referred for cadaveric examination, which revealed all the permanent teeth fully erupted in the oral cavity. Among the distinctive dental traits, occlusal amalgam restorations were observed in the mandibular first molars, as well fixed orthodontic appliances with bands in the same teeth. Intraoral photographs were provided by the relatives of the potential victim. In these photographs, the same distinctive dental traits were observed leading to a positive identification without explainable discrepancies. The use of intraoral photographs for forensic purposes must be encouraged in medico-legal institutes because these are practical, low-cost, absent of radiation and reliable tools in the human identification process.